Multi-Channel 4D Parametrized Atlas of Macro- and Microstructural Neonatal Brain Development - Uus, Alena; Grigorescu, Irina; Pietsch, Maximilian; Batalle, Dafnis; Christiaens, Daan; Hughes, Emer; Hutter, Jana; Cordero Grande, Lucilio; Price, Anthony N.; Tournier, Jacques-Donald; Rutherford, Mary A.; Counsell, Serena J.; et al. (Frontiers in Neuroscience, 2021)
Structural (also known as anatomical) and diffusion MRI provide complimentary anatomical and microstructural characterization of early brain maturation. However, the existing models of the developing brain in time include only either structural or diffusion MRI channels. Furthermore, there is a lack of tools for combined analysis of structural and diffusion MRI in the same reference space. In this work, we propose a methodology to generate a multi-channel (MC) continuous spatio-temporal parametrized atlas of the brain development that combines multiple MRI-derived parameters in the same anatomical space during 37–44 weeks of postmenstrual age range. We co-align structural and diffusion MRI of 170 normal term subjects from the developing Human Connectomme Project using MC registration driven by both T2-weighted and orientation distribution functions channels and fit the Gompertz model to the signals and spatial transformations in time. The resulting atlas consists of 14 spatio-temporal microstructural indices and two parcellation maps delineating white matter tracts and neonatal transient structures. In order to demonstrate applicability of the atlas for quantitative region-specific studies, a comparison analysis of 140 term and 40 preterm subjects scanned at the term-equivalent age is performed using different MRI-derived microstructural indices in the atlas reference space for multiple white matter regions, including the transient compartments. The atlas and software will be available after publication of the article1.
CRIS-Team Scopus Importer:2023-03-08
Keywords: atlas-based analysis; multi-channel registration; multi-modal MRI; neonatal brain; spatio-temporal atlas; white matter maturation; white matter parcellation